Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Masyarakat pada Kantor Kelurahan Matalamagi Sorong - Sinay, Philipus; Maryen, Andrei; Sakalessy, Brando Charles (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to assess the impact of service quality and facilities on citizen satisfaction at the Matalamagi Village Office in Sorong. The approach applied in data processing is quantitative descriptive analysis. The partial t-test results indicate that service quality has a positive and significant effect on the dependent variable, with a t-value of 5.994, exceeding the t-table value of 1.6716, and a significance level of 0.000, which is less than 0.05. Therefore, hypothesis (H1) is accepted. Similarly, the facilities variable has a t-value of 3.033, which is greater than the t-table value of 1.6716, with a significance level of 0.000 < 0.05, leading to the acceptance of hypothesis (H2). Furthermore, the F-test results show that the F-value reaches 48.918 with a significance level of 0.000, which is less than 0.05. This confirms that, simultaneously, service quality and facilities influence citizen satisfaction.